Study on Shear Creep Characteristics and Creep Model of Soil-Rock Mixture Considering the Influence of Water Content - Jiang, Zihua; Wang, Huanling (Frontiers in Physics, 2022)
Water content has a significant effect on the creep properties of soil-rock mixtures (SRM). Multi-loading shear creep tests are carried out on SRM samples with different water contents. The test results show that deformation gradually increase with increasing water content, while long-term strength gradually decrease with increasing water content. The deformation mechanism shows that increasing of water content causes the change of rock particles at on the shear surface from fracture to rotation. Based on the creep test results, a modified Burgers model considering the water content is proposed by the empirical relationship between the parameters of the traditional Burgers model and the water content. And the results predicted by the modified Burgers model agree well quite well with the experimental creep data.